The material culture of Hlubi male initiation: a case study from Matatiele, Eastern Cape, South Africa - Zulu, John (My University, 2016)
This is a study of the material culture associated with male circumcision rituals among Hlubi people in the Matatiele region of South Africa’s Eastern Cape Province. In recent years social scientists and public commentators have paid increasing attention to male circumcision in the context of controversies around ‘botched’ circumcisions, on the one hand, and the growing evidence, on the other hand, that male circumcision plays a role in restricting the spread of HIV. Much less attention has been paid, however, to a vital issue that underpins all these concerns: what materials give male circumcision its distinctive qualities as a cultural process, and how do various kinds of participants and observers think about those materials in relation to other domains of material culture, e.g. medical circumcision. This study will approach the topic through unstructured interviews conducted with various groups of informants
A dissertation submitted in fulfillment of the requirements for the award of the Degree of Master of Social Sciences in the Department of Anthropology Faculty of Humanities University of the Witwatersrand March 2016
Keywords: Hlubi (African people)--Social life and customs; Initiation rites--South Africa; Circumcision--South Africa; Circumcision--Social aspects--South Africa